Impact of Steroid Only Induction on Rejection in Simultaneous Liver-Kidney Transplantation. (December 2022) - Ruiz, Irene; Sparkes, Tracy; Masters, Brian; Barth, Rolf; Maluf, Daniel; Freedman, Sari
Introduction: The occurrence of simultaneous liver kidney transplantation has greatly increased; however, the ideal induction and maintenance immunosuppression remains unknown.Question: This evaluation aimed to determine if corticosteroid only induction in simultaneous liver kidney transplant recipients provided adequate prophylaxis against rejection when compared to basiliximab.Design: This was a single center, retrospective, cohort study of adult simultaneous liver kidney transplant recipients from June 2010 to June 2019 receiving corticosteroid only (N = 41) or basiliximab (N = 42) induction.Results: Liver or kidney biopsy proven acute rejection at 3 months was comparable between the corticosteroid only and basiliximab groups (10% vs 7%, P = .67), which persisted through 12 months posttransplant (15% vs 21%, P = .42). The occurrence of any infection at 3 months was increased in the corticosteroid only group relative to the basiliximab group (41% vs 21%, P = .049). Graft and patient survival at 12 months were similar between groups. Maintenance immunosuppression was overall minimized with a tacrolimus goal of 6-8 ng/mL, mycophenolate mofetil dose reduction to 1000 mg/day by 3 months, and early steroid withdrawal in both groups.Conclusion: Our findings suggested that corticosteroid only induction was an effective strategy for preventing rejection in simultaneous liver kidney transplant recipients, even in combination with reduced maintenance immunosuppression.